Exploration of Physics Concepts in Game Vehicles in the Indonesian Fantasy World - Adinda Choirunnisa'; Nauly Rahmaniyah; Qori Aina (Studies in Philosophy of Science and Education, 2021)
Edutainment in physics learning or also known as physics-edutainment is a physics learning strategy associated with entertainment. The purpose of this article is to explore the physics concepts contained in the Indonesian Fantasy World. The research was conducted by studying literature from various sources of supporting articles. This study uses a qualitative descriptive approach, while the type of research used by the researcher is library research. Data or information in the form of articles obtained, then analyzed according to the content or purpose of each article. The data obtained is that there are 6 game rides that have been explored, including the Kora-kora, Bianglala, Halilintar, Ontang-anting, Zig-zag, and Hysteria rides which have physics concepts in the techniques used when moving them.